Otimização e validação da quantificação de malondialdeído plasmático por cromatografia líquida de alta eficiência com detecção visível - Grotto, Denise (2007)
The overproduction of reactive oxygen and nitrogen species or the reduction in the antioxidant capacity results in the oxidative stress. The lipid peroxidation involves the oxidative deterioration of polyunsaturated fatty acids and it process is involved in the pathogenesis of diseases such as cancer, diabetes, atherosclerosis and neuro-degenerative diseases. Since it is complex to carry out the free radical quantification directly in vivo, it is necessary to do the measure of their reaction products and the malondialdehyde (MDA) is one of the most known secondary products of the lipid peroxidation used as an indicator of cell membrane injury. The MDA has been measured by its reaction with the thiobarbituric acid (TBA), which produces the MDA-TBA2 complex that can be detected by spectrophotometry method known such thiobarbituric acid reactive substances (TBARS). However, the major problem in this method is the lack of specificity, once TBA reacts with a variety of compounds, overestimating the real levels of MDA. Thus, methods involving high performance liquid chromatography (HPLC) have been reported, which are specifics and sensitive. In this study, a rapid and reliable method was optimized and validated to quantify plasmatic MDA by HPLC, using visible detection. The analytical parameters evaluated were: linearity, precision, accuracy, recovery, sensibility, robustness, and stability. The optimized method was applied in subjects from a retirement home in Santa Maria. The plasma sample underwent alkaline hydrolysis with NaOH, to a complete release of protein bound to the MDA, followed to acid deproteinization with H3PO4 and derivatization with TBA. To removal of interferents, a sample extraction with n-butanol before the chromatographic injection was carried out. The MDA analysis was performed in a C18 column, integrated with a guard-column. The mobile phase was constituted by KH2PO4 2.5 mM and methanol (50:50), with isocratic elution and detection at 532 nm. The assay was linear from 0.28 to 6.6 μM. The precisions intra and inter-day were obtained with CV% < 4% and < 11%, respectively. The accuracy (bias%) ranged from -4.1 to 2% and the recovery ranged from 95.9 to 102.7%. The limit of detection was 0.05 μM and the limit of quantification was 0.17 μM. For the stability test, it was observed that the MDA standard solutions were stable for, at least, 18 months at -20ºC. The plasma sample was stable for 24h when it was stored at -20ºC, but it was not stable at 4ºC. After alkaline hydrolysis storage at -20ºC, plasmatic MDA was not stable; on the other hand, the sample remained stable for 30 days after TBA reaction storage at -20ºC. After n-butanol extraction storage, the MDA levels were stable for 3 days at -20ºC. The method was applied in plasma samples in healthy subjects from 60 to 80 years. The elderly subjects had MDA plasma levels of 4.45 ± 0.81 μM for women and 4.60 ± 0.95 μM for men, without a significant difference. These levels were considered such as reference values to this age in our laboratory. Thus, the results demonstrated that a simple, rapid and specific technique was optimized and validated. The method showed to be consistent in all analytical parameters and can be used in the routines in clinical laboratories.